Correlation Between Birth Weight and Exclusive Breastfeeding with Stunting in Children Aged 6–24 Months - Husnul Muthoharoh; Siti Sholikha; Kustini Kustini; Asyaul Wasiah; Lilik Darwati; Dellamitha Arifiah Muslim (Universitas Muhammadiyah Sidoarjo, 2025)
Stunting remains a chronic nutritional issue in Indonesia, particularly among children under the age of two. Two crucial factors influencing stunting status are birth weight and exclusive breastfeeding. This study aims to determine the correlation between birth weight, exclusive breastfeeding, and stunting in children aged 6–24 months. This study employed an analytical quantitative design with a cross-sectional approach. A total of 120 children aged 6–24 months and their mothers were selected using purposive sampling at Deket Community Health Center Lamongan. Data were collected through interviews using structured questionnaires and anthropometric measurements. Data analysis was conducted using chi-square tests and logistic regression. The analysis revealed a significant association between birth weight and stunting (p = 0.003), and a significant association between exclusive breastfeeding and stunting (p = 0.001). Children with low birth weight (<2500 grams) had a 3.1 times higher risk of stunting, while children who were not exclusively breastfed had a 2.7 times higher risk of stunting compared to those who were exclusively breastfeed. Although the study provides valuable insights, its cross-sectional nature limits causal interpretation, and recall bias may have affected the accuracy of reported breastfeeding practices. Despite these limitations, the findings underscore the need for strengthened prenatal and breastfeeding interventions to prevent stunting. Birth weight and exclusive breastfeeding are significantly associated with stunting in children aged 6–24 months. Promotive and preventive interventions through pregnancy monitoring and breastfeeding education are crucial efforts in preventing stunting.